Young Human Cholinergic Neurons Respond to Physiological Regulators and Improve Cognitive Symptoms in an Animal Model of Alzheimer’s Disease - Morelli, Annamaria; Sarchielli, Erica; Guarnieri, Giulia; Coppi, Elisabetta; Pantano, Daniela; Comeglio, Paolo; Nardiello, Pamela; Pugliese, Anna M.; Ballerini, Lara; Matucci, Rosanna; Ambrosini, Stefano; Castronovo, Giuseppe; et al. (Frontiers in Cellular Neuroscience, 2017)
The degeneration of cholinergic neurons of the nucleus basalis of Meynert (NBM) in the basal forebrain is associated to the cognitive decline of Alzheimer's disease (AD) patients. To date no resolutive therapies exist. Cell-based replacement therapy is a strategy currently under consideration, although the mechanisms underlying the generation of stem cell-derived NBM cholinergic neurons able of functional integration remain to be clarified. Since fetal brain is an optimal source of neuronal cells committed towards a specific phenotype, this study is aimed at isolating cholinergic neurons from the human fetal NBM (hfNBMs) in order to study their phenotypic, maturational and functional properties. Extensive characterization confirmed the cholinergic identity of hfNBMs, including positivity for specific markers (such as choline acetyltransferase) and acetylcholine (Ach) release. Electrophysiological measurements provided the functional validation of hfNBM cells, which exhibited the activation of peculiar sodium (INa) and potassium (IK) currents, as well as the presence of functional cholinergic receptors. Accordingly, hfNBMs express both nicotinic and muscarinic receptors, which were activated by Ach. The hfNBMs cholinergic phenotype was regulated by the nerve growth factor (NGF), through the activation of the high-affinity NGF receptor TrkA, as well as by 17-β-estradiol through a peculiar recruitment of its own receptors. When intravenously administered in NBM-lesioned rats, hfNBMs determined a significant improvement in memory functions. Histological examination of brain sections showed that hfNBMs (labeled with PKH26 fluorescent dye prior to administration) reached the damaged brain areas. The study provides a useful model to study the ontogenetic mechanisms regulating the development and maintenance of the human brain cholinergic system and to assess new lines of research, including disease modelling, drug discovery and cell-based therapy for AD.